PENGARUH MODEL PEMBELAJARAN INTRODUCTION CONNECTION APPLICATION REFLECTION DAN EXTENSION (ICARE) TERHADAP KEMAMPUAN PEMECAHAN MASALAH DAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI ARITMATIKA SOSIAL DI KELAS VII SMPIT DARUL FIKRI BENGKULU UTARA - Yuliani Nasution; Agus Susanta; Zamzaili Zamzaili; Saleh Haji (LPPM Universitas Bina Bangsa, 2023)
This study aims to determine the effect of the Intruction Connection Application Reflection and Extention (ICARE) Learning Model on Students' Problem-Solving Ability and Critical Thinking Ability. This type of research uses the Quasi Experiment method. Data collection is done through tests. Data analysis used the Ancova test. The sample of this study were students of SMPIT Darul Fikri Bengkulu Utara grades VII A and VII B. The results showed that: 1) There was a linear covariate effect of initial ability on problem solving ability with a significant influence of 50.3%. 2) There is a linear influence of the initial ability covariate on critical thinking skills with a large influence of 56.7%. 3) There is an effect of learning using the ICARE model on students' problem-solving abilities with a large influence of 59.9%. 4) There is an influence of learning using the ICARE model on students' critical thinking skills with a large influence of 59.4%.